2019
DOI: 10.1093/scan/nsz047
|View full text |Cite
|
Sign up to set email alerts
|

Predictability modulates the anticipation and perception of pain in both self and others

Abstract: Predictability has been suggested to modulate both the anticipation and perception of self-pain. Considering the overlapping neural circuits between self-pain and other-pain perceptions, the present study investigated how the predictability of forthcoming pain modulates the anticipation and perception of self-pain and other-pain. We used a balanced, within-participant experimental design in which a visual cue indicating the recipient, intensity and predictability of an upcoming painful electrical stimulation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…For example, the common prescription painkiller acetaminophen can reduce empathy for others' pain (Mischkowski et al, 2016), suggesting that pharmacologically inhibiting the neural circuits necessary for experiencing one's own pain also inhibits the perception/experience of others' pain. Further, electroencephalographic (EEG) studies have shown similar modulations of self and other‐related pain processing (Meng et al, 2013; Peng, Huang, Liu, & Cui, 2019; Rütgen, Seidel, Riečanský, & Lamm, 2015), for example, placebo analgesia induction procedure equivalently reduces behavioral responses and the affective‐motivational P2 component on event‐related potentials (ERPs) to self and other‐related pain (Rütgen, Seidel, Riečanský, et al, 2015). The evidence for the association between the perception of first‐hand pain and others' pain predicts shared sensitivity to first‐hand physical pain and empathy for others' pain.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the common prescription painkiller acetaminophen can reduce empathy for others' pain (Mischkowski et al, 2016), suggesting that pharmacologically inhibiting the neural circuits necessary for experiencing one's own pain also inhibits the perception/experience of others' pain. Further, electroencephalographic (EEG) studies have shown similar modulations of self and other‐related pain processing (Meng et al, 2013; Peng, Huang, Liu, & Cui, 2019; Rütgen, Seidel, Riečanský, & Lamm, 2015), for example, placebo analgesia induction procedure equivalently reduces behavioral responses and the affective‐motivational P2 component on event‐related potentials (ERPs) to self and other‐related pain (Rütgen, Seidel, Riečanský, et al, 2015). The evidence for the association between the perception of first‐hand pain and others' pain predicts shared sensitivity to first‐hand physical pain and empathy for others' pain.…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out by Singer et al, the ability to experience other people's pain is a core feature of empathy [27]. Pain empathy is grounded in people's first-hand experiences of pain, given that the perceptions of one's own pain and another's pain are subserved by overlapping neurocomputational functions [28][29][30] and that they can be similarly modulated by psychological and pharmacological factors (e.g., placebos) [30,31]. Physical painkillers (e.g., acetaminophen) reduce empathy for others' pain via the same neural pathways that alleviate one's own pain [32].…”
mentioning
confidence: 99%
“…Mediation analysis further revealed that tRNS application attenuated perceived-pain ratings partially via the drop in expected-pain ratings. With the knowledge that a painful event is upcoming, selective attention could be more precisely directed toward processes related to forthcoming sensorimotor events [53,54], which might manifest as suppression of cortical alpha oscillations [29,55,56]. An EEG study has reported that tRNS increases cortical alpha oscillations [57], whereby increased alpha oscillation has been associated with decreased attention resource allocation [58].…”
Section: Fig 3 Immediate Effects Of Tes On Perceived-pain Ratingsmentioning
confidence: 99%